Adaptation Mechanisms in the Evolution of Moss Defenses to Microbes - Ponce de León, Inés; Montesano, Marcos (Frontiers in Plant Science, 2017)
Bryophytes, including mosses, liverworts and hornworts are early land plants that have evolved key adaptation mechanisms to cope with abiotic stresses and microorganisms. Microbial symbioses facilitated plant colonization of land by enhancing nutrient uptake leading to improved plant growth and fitness. In addition, early land plants acquired novel defense mechanisms to protect plant tissues from pre-existing microbial pathogens. Due to its evolutionary stage linking unicellular green algae to vascular plants, the non-vascular moss Physcomitrella patens is an interesting organism to explore the adaptation mechanisms developed in the evolution of plant defenses to microbes. Cellular and biochemical approaches, gene expression profiles, and functional analysis of genes by targeted gene disruption have revealed that several defense mechanisms against microbial pathogens are conserved between mosses and flowering plants. P. patens perceives pathogen associated molecular patterns (PAMPs) by plasma membrane receptor(s) and transduces the signal through a MAP kinase cascade leading to the activation of cell wall associated defenses and expression of genes that encode proteins with different roles in plant resistance. After pathogen assault, P. patens also activates the production of ROS, induces a HR-like reaction and increases levels of some hormones. Furthermore, alternative metabolic pathways are present in P. patens leading to the production of a distinct metabolic scenario than flowering plants that could contribute to defense. P. patens has acquired genes by horizontal transfer from prokaryotes and fungi, and some of them could represent adaptive benefits for resistance to biotic stress. In this review, the current knowledge related to the evolution of plant defense responses against pathogens will be discussed, focusing on the latest advances made in the model plant P. patens.